2003
DOI: 10.1097/01.tp.0000065178.93741.72
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the spectrum and risk factors for invasive candidiasis in liver transplant recipients: prospective, multicenter, case-controlled study1

Abstract: Our study has identified predictors for Candida infections in the current era that have implications relevant for targeting the prophylaxis toward the high-risk patients. Routine use of antifungal prophylaxis warrants concern given the emergence of non-albicans Candida spp. as significant pathogens after liver transplantation and higher mortality in patients with these infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
157
5
15

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(191 citation statements)
references
References 28 publications
14
157
5
15
Order By: Relevance
“…The gastrointestinal tract is often colonized with candidal species and is the most likely portal of entry, via translocation through the intestinal walls to extraluminal locations or due to spillage from bowel anastomosis. 59,60 Candida may cause intra-abdominal abscesses, peritonitis, or may disseminate hematogenously to other organs. Need of hemodialysis post-operatively, prophylaxis for spontaneous bacterial peritonitis, and retransplantation are important risk factors for invasive candidiasis.…”
Section: Correct Answers: a C And Dmentioning
confidence: 99%
“…The gastrointestinal tract is often colonized with candidal species and is the most likely portal of entry, via translocation through the intestinal walls to extraluminal locations or due to spillage from bowel anastomosis. 59,60 Candida may cause intra-abdominal abscesses, peritonitis, or may disseminate hematogenously to other organs. Need of hemodialysis post-operatively, prophylaxis for spontaneous bacterial peritonitis, and retransplantation are important risk factors for invasive candidiasis.…”
Section: Correct Answers: a C And Dmentioning
confidence: 99%
“…Candida albicans is the most common isolated species followed by Candida glabrata and Candida tropicalis. 43,44 The gastrointestinal tract is often colonized with candidal species and those with advanced liver disease/cirrhosis may be predisposed to supercolonization. One study of potential orthotopic liver transplant recipients identified colonization with candida species in all subjects at varying locations in the alimentary canal.…”
Section: Candidamentioning
confidence: 99%
“…[46][47][48] Risk factors for invasive candidiasis include the use of prophylactic antibiotics to prevent spontaneous bacterial peritonitis, the need for renal replacement therapy (hemodialysis) postoperatively, and retransplantation. 44 Other potential risk factors include technically complicated and lengthy transplantation operative procedures, intraoperative transfusion, prolonged ICU admission, repeated intra-abdominal surgery after transplantation, Candida colonization, and cytomegalovirus disease. 48 CMV disease is a clear risk factor for all types of invasive candidal infections, and effective prophylaxis of patients at high risk for CMV disease, such as those who are CMV D+/ RÀ (donor positive, recipient negative), has been shown to significantly decrease the incidence of invasive Candida infection in the absence of specific anti-Candida prophylaxis.…”
Section: Candidamentioning
confidence: 99%
See 1 more Smart Citation
“…Im Zusammenhang mit systemischen Mykosen wurden für Transplantationspatienten als Risikofaktoren eine präoperative Kolonisation mit Candida, ein pulmonaler Aspergillus-Nachweis (Lungentransplantation), eine Retransplantation, eine lange Operationsdauer (>5 h) mit hohem Blutverlust/ Massivtransfusion [19,28], ein langer Intensivaufenthalt zusammen mit der Notwendigkeit der Anlage invasiver Katheter (Z. B. zentraler Venen-, Dialysekatheter, Drainagen, Stents; [10,18,20,28]), der Einsatz von Breitspektrumantibiotika, ein Nierenversagen (ggf. Hämofiltration bzw.…”
Section: Grundlagenunclassified